Host–Guest Doping in Flexible Organic Crystals for Room‐Temperature Phosphorescence. (18th January 2023) - Xia, Yang; Zhu, Chenfei; Cao, Feng; Shen, Yunxia; Ouyang, Mi; Zhang, Yujian
Abstract: Organic single crystals (OSCs) with excellent flexibility and unique optical properties are of great importance due to their broad applicability in optical/optoelectronic devices and sensors. Nevertheless, fabricating flexible OSCs with room‐temperature phosphorescence (RTP) remains a great challenge. Herein, we propose a host–guest doping strategy to achieve both RTP and flexibility of OSCs. The single‐stranded crystal is highly bendable upon external force application and can immediately return to its original straight shape after removal of the stress, impressively emitting bright deep‐red phosphorescence. The theoretical and experimental results demonstrate that the bright RTP arises from Förster resonance energy transfer (FRET) from the triphenylene molecules to the dopants. This strategy is both conceptually and synthetically simple and offers a universal approach for the preparation of flexible OSCs with RTP. Abstract : The integration of flexibility and room‐temperature phosphorescence in an organic single crystal is achieved by the host–guest doping strategy. The centimeter‐scale crystals can be repeatedly bent and emit deep‐red afterglow. This phenomenon occurs because the guest molecules, as trace impurities, greatly affect the emission properties of the materials, whereas the effect on the molecular packing of the host molecules is negligible.